OCB Analysis, Transformational Leadership Style, Work Ethic, Work Satisfaction, And Good Governance - Iha Haryani Hatta, Widarto Rachbini, Dian Riskarini, Yuana Rizky Octaviani Mandagie (Jurnal Manajemen, 2018)
The existence of factors that improve employee job satisfaction will support the achievement of good governance. Therefore, study is needed on the analysis of organizational citizenship behavior (OCB), transformational leadership style, work ethic, job satisfaction, and good governance with the aim of knowing the effect of OCB, transformational leadership style, and work ethic partially on job satisfaction and good governance; the influence of job satisfaction on good governance. This study uses 200 respondents of sub-district office staff in DKI Jakarta who were selected using multistage sampling techniques. Data processing used SEM, Lisrel Program. The results showed that transformational leadership style had an effect on job satisfaction, but OCB and work ethic had no effect on job satisfaction; OCB, work ethic, and job satisfaction affect good governance, but transformational leadership style does not affect good governance.